The Effect of Semi-cooperative Strategy in the Achievement of Fifth Grade Students in the Subject of Philosophy and Psychology and the Improvement of Their Scientific Exploration - Saleh Al-Jubouri, Rahel Ajam (Journal of Tikrit University for Humanities, 2024)
The aim of this study is to discover the effect of cooperative learning in the achievement of the fifth year students in the literary branch and to improve their scientific exploration. In order to achieve the objectives of the study, the researcher adopted the semi-experimental design. The sample of the study was consisted of 70 students who studied in ibn Al-Atheer Preparatory school in Al-Alam city. They were divided into two groups: the control and the experimental group. Equivalence between the two groups was made according to the variables of age, the previous study, intelligence, and the academic achievement of parents. The researcher thinks that these variables have impact upon the dependent variables.